Porque eu sou é homem: a representação do masculino na publicidade brasileira na década de 1970 e nos anos 2000 - Furtado, Juliana de Assis (2008)
Currently, it is experienced the transition from a solid society, where structures tended to be stable and individual identities seemed to be fixed, into a liquidity, which transforms what is durable into transitory and makes identities mobile and multiple. The human being transits through a real cultural supermarket, in whose shelves it is possible to select them. This happens in the late capitalism sphere, period when it is remarkable the need for expanding markets and where advertising works as a marketing strategy. As a tool that goes beyond the simple information transmission, it expresses values with which its audience identifies. A product is bought to satisfy a material need, but also to assure a personality. In this scenario, this thesis observes advertising not only as a media production, but also as a cultural text that is influenced by the social, political and economic context where it is created, influencing it in a reciprocal process. Based on the French discourse analysis and its key concept of conditions of production, this thesis approaches two historical moments lived by Brazilian society: the 1970 decade, period of the military dictatorship, the feminist movement, the increasing industrialization and the arising of the first masculine magazines, and the 2000 years, time of liberal economic politics and stable currency, new technologies, new relationship and aesthetic standards. Thus, it develops the analysis of examples of advertising that targets the masculine audience, disclosed in the newspaper media during both periods, comparing the way through which this media text represented and represents masculine identity in the country. In the supermarket corridors from the beginning of the XXI century, it is possible to notice that it has moved, having reconfigured itself within the non-static modernity where it lives